B cell activating factor is induced by toll-like receptor and NOD-like receptor-ligands and plays critical role in IgM synthesis in Labeo rohita. (October 2016) - Basu, Madhubanti; Lenka, Saswati S; Paichha, Mahismita; Patel, Bhakti; Banerjee, Rajanya; Das, Surajit; Jayasankar, Pallipuram; Samanta, Mrinal
Highlights: BAFF has been cloned and characterized in the Indian major carp rohu ( Labeo rohita) . BAFF gene expression in rohu is induced in response to TLR and NLR-ligands. Recombinant-BAFF is shown to induce IgM synthesis in fish through BAFF-R. BAFF may be used as an effective therapeutic candidate against fish diseases. Abstract: B-cell activating factor (BAFF), an important member of the tumor necrosis factor superfamily, plays critical roles in the modulation of B-cell functions and enhancement of immune response in the host. Like higher vertebrates, the important role of BAFF in boosting immune response against diverse pathogens was also envisaged in fishes. We therefore, studied BAFF in rohu ( Labeo rohita ), a freshwater food fish species of highest economic importance in the Indian subcontinent. Full-length rohu-BAFF- cDNA comprised of 804 bp nucleotide long ORF, encoding 267 amino acid residues, and shared high structural similarity with human-BAFF. It was expressed in the embryonic developmental stages suggesting its key role in immune response at the early life of fish. In Aeromonas hydrophila infection and rhabdoviral antigen stimulation, BAFF-gene expression in rohu was induced across the organs/tissues. Stimulation of un-treated healthy rohu fish leukocytes, and viral or bacterial or BSA (bovine serum albumin) antigen stimulated rohu fish leukocytes with recombinant-BAFF (r-BAFF) resulted in enhanced expression of immunoglobulin (Ig)M. Both in-vitro and in-vivo treatment with toll-like receptor (TLR)- ligand (poly I:C) or nod-like receptor (NLR)- ligands (iE-DAP and MDP) resulted in TLR and NLR activation and BAFF-gene expression. This is the first report showing BAFF-expression by innate immune receptor-ligands and its critical role in enhancing adaptive immune response in fish.